OPTIMIZING THE ROLE OF BAWASLU IN PREVENTING VIOLATIONS IN THE IMPLEMENTATION OF ELECTIONS - Zainuddin, Zainuddin (Proceeding International Seminar of Islamic Studies, 2024)
Bawaslu is a permanent institution, the term of office of its members is 5 (five) years from the date of oath or appointment. Bawaslu or Panwaslu is an ad hoc institution formed before the first stage of the election, namely the voter registration stage which begins and ends after the nomination of the selected candidate. The election monitoring body is unique in Indonesia because Bawaslu was formed to monitor the implementation of the election stages, receive complaints and handle administrative irregularities and election crimes. The authority to supervise the implementation of elections is given to Bawaslu and the ranks below it. Supervision is one of the most important factors in determining the success or failure of an election. Election supervision is the activity of observing, studying, examining and assessing the process of election organizers in accordance with statutory regulations. Bawaslu at all levels has an important role in ensuring that elections are held democratically in a direct, public, free, confidential, honest and fair manner in accordance with applicable laws and regulations. Based on research results, optimizing the role of Bawaslu in preventing election violations is a collective effort. By uniting the power of community outreach, cooperation with related institutions, strengthening technology, improving human resources, and community participation, Bawaslu can be at the forefront of protecting Indonesian democracy from the risk of election violations.